Synthesis, Antibacterial and Antiribosomal Activity of the 3C-Aminoalkyl Modification in the Ribofuranosyl Ring of Apralogs (5-O-Ribofuranosyl Apramycins) - Dmitrijs Lubriks; Klara Haldimann; Sven N. Hobbie; Andrea Vasella; Edgars Suna; David Crich (MDPI AG, 2022)
The synthesis and antiribosomal and antibacterial activity of both anomers of a novel apralog, 5-O-(5-amino-3-C-dimethylaminopropyl-D-ribofuranosyl)apramycin, are reported. Both anomers show excellent activity for the inhibition of bacterial ribosomes and that of MRSA and various wild-type Gram negative pathogens. The new compounds retain activity in the presence of the aminoglycoside phosphoryltransferase aminoglycoside modifying enzymes that act on the primary hydroxy group of typical 4,5-(2-deoxystreptamine)-type aminoglycoside and related apramycin derivatives. Unexpectedly, the two anomers have comparable activity both for the inhibition of bacterial ribosomes and of the various bacterial strains tested.